Pemberdayaan Masyarakat Melalui Program Kampung Sejahtera Mandiri (KSM) dalam Mewujudkan Kesejahteraan Sosial (Studi Kasus di Kampung Grenpul Kelurahan Gerendeng Kecamatan Karawaci) - Rimadina Melianingsih; Muhtadi Muhtadi Muhtad (UIN Siber Syekh Nurjati Cirebon, 2022)
This study looks at how the sustainability of community empowerment through the Mandiri Prosperous Village (KSM) program in Grenpul Village is seen from the stages, results, and supporting and inhibiting factors of the community empowerment process through the Mandiri Prosperous Village (KSM) program in realizing social welfare. The method used in this research is descriptive qualitative with data collection techniques using observation, interviews, and documentation studies. The results of this study indicate that community empowerment through the Kampung Sejahtera Mandiri (KSM) program has been able to realize social welfare in the community in Grenpul Village. This can be seen from the welfare indicators used as a measure of success in community empowerment through the Mandiri Prosperous Village (KSM) program. In addition, it can be seen from the seven stages of the community empowerment process through the Kampung Sejahtera Mandiri (KSM) program including the preparation, assessment, planning alternative programs or activities, formulation of action plans, implementation of programs or activities, evaluation, and termination which have gone well even though There are several stages that are not fully in accordance with the existing theory. In this case, of course there are supporting factors and inhibiting factors in the sustainability of community empowerment through the Mandiri Prosperous Village (KSM) program.